Mathematical modeling of the epidemic diseases - Askouni, A.; Doulopoulou, E.; Argyri, P. (Open Schools Journal for Open Science, 2020)
Biology and mathematics are key lessons in our curriculum from elementary to high school. Biology science studies the structure and evolution of living organisms and is directly linked to human life on the planet. Many of us have been wondering, "Why do we learn Math?" And "Where will they serve us?" In this work, by linking the courses of Biology and Mathematics, we highlight the role and value of mathematical science in analyzing and explaining real-world situations and phenomena. The experiment we conducted in three classrooms of our school, enabled us to mathematical modeling of infectious diseases, to draw conclusions, to motivate us to further research mathematical models and simulations that would interpret real-world conditions and contemporary ones. Therefore, it will help in making decisions and preventive measures.